COMPANY LEADERSHIP NARCISSISM ON INTERNAL CONTROL (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
This study aims to examine the effect of company leadership narcissism on the company's internal control. The sampling technique used was purposive sampling. Data were obtained as many as 429 samples from the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. Panel data regression with random effects model was used to analyze the research data. The results of this study indicate that there is no significant effect of company leadership narcissism on internal control.